THE INFLUENCE OF TECHNOLOGICAL TRAINING ON ENTREPRENEURSHIP AND THE SUCCESS OF MICRO, SMALL AND MIDDLE BUSINESS TENANT OF BUSINESS AND TECHNOLOGY INCUBATOR (BTI) JAMBI UNIVERSITY - Novita Eka Sari (Journal of Business Studies and Management Review, 2018)
The aim of this research is to know and analyze Whether the entrepreneurship and technological training that had already Gave by the business and technology incubator (BTI) of Jambi University Reviews their meet purpose is to Increase the success of micro, small and middle business. This micro, small and middle business that uses as a sample of this research was the one that already Becomes members of the BTI of Edinburgh University, they were called outwall tenant and the number of this sample is 28, a businessman/woman. This research uses a fishbone diagram to describe the research from the beginning to the end, using reliability and validity test to every question and to analyze the influence of variables researcher uses the multiple regression using SPSS statistical method. The result shown that all the sub-variables of Training (Reaction, Learning, Behavior, Result) had simultaneously influence the success of micro, small and middle business of BTI outwall tenants about 91.8% and only 8.2% influenced by other factors that is not include in this research, in the other hand, partially the sub-variables that give the most influenced Reaction was with the percentage of 87.3%.